Origins : on the genesis of psychic reality - Mills, Jon, 1964- (McGill-Queen's University Press, 2010)
""Origins is an intriguing and ambitious work. Jon Mills wants to do no less than develop a new, dialectical psychology that will shake the assumptions of self-satisfied psychologists and philosophers. The controversial nature of this book is one of its signal strengths." John Lachs, Centennial Professor Of Philosophy, Vanderbilt University." "The question of what constitutes psychic reality has been of interest to philosophers and psychologists for as long as humans have thought about the mind. In Origins, Jon Mills presents a provocative challenge to contemporary theories about the difference between the mind and body. By re-examining our understanding of the unconscious, Mills explains the birth of the psyche and provides a detailed account of the ways in which subjectivity is formed." "The first comprehensive work to articulate a psychoanalytic metaphysics based on process thought, the author uses dialectical logic to show how the nature and structure of mental life is constituted. Arguing that ego development is produced not only by consciousness but also evolves from unconscious genesis, he makes the controversial claim that an unconscious semiotics serves as the template for language and all meaning structures." "A thought-provoking account of idealism, Origins confronts the limitations of materialism and empiricism while salvaging the roles of agency and freedom that have been neglected by the biological sciences."--Jacket